2014
DOI: 10.1080/1369183x.2014.930660
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Your Country: Networks, Perceptions and Destination Selection among Georgian Labour Migrants

Abstract: Existing literature demonstrates that social networks play a key role in international migrants' selection of destinations. But how do such networks begin? The Republic of Georgia is an example of a country from which migrants travel to many different destination countries, most of which had no Georgian population before the collapse of the Soviet Union. This paper uses a combination of nationally representative survey data and semi-structured interviews to identify the patterns and logic of men's and women's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In the literature on international migration it is suggested that people are attracted by countries rather than by particular localities, as individuals generally move to localities where there are job opportunities (e.g. Geis, Uebelmesser, & Werding, 2013;Hofmann, 2015;Moral-Pajares & Jiménez-Jiménez, 2014;Palmer & Pytliková, 2015). Nevertheless, we argue this might not hold true for exchange students.…”
Section: Introductionmentioning
confidence: 42%
“…In the literature on international migration it is suggested that people are attracted by countries rather than by particular localities, as individuals generally move to localities where there are job opportunities (e.g. Geis, Uebelmesser, & Werding, 2013;Hofmann, 2015;Moral-Pajares & Jiménez-Jiménez, 2014;Palmer & Pytliková, 2015). Nevertheless, we argue this might not hold true for exchange students.…”
Section: Introductionmentioning
confidence: 42%
“…Gender norms play significant roles in migrant families as a means of determining migration patterns under the household strategy, with sons chosen for labor migration while daughters are bonded to domestic work and agricultural production (Pei and Cong 2019;Tong et al 2019). This gender ideology in the migration process has been observed in Confucian countries such as China (Chiang et al 2015) and Vietnam (Hoang 2011), as well as in non-Confucian countries such as Mexico (Schmalzbauer 2011) and Georgia (Hofmann 2015). Granted that women exert agency in the migration decision-making process, their own migration may be limited because they must negotiate for their interests to preserve family harmony (Hoang 2011).…”
Section: Gendered Migration and Family Gender Rolesmentioning
confidence: 99%
“…Migrants must weigh their existing financial, human, and social capital against their ability to reach and thrive in a more desirable migration destination. With this in mind, there is potential for different types of migrants from the same sending context (Venezuela) to seek out different destination countries based on their financial, human, and social capital (Hofmann, 2015).…”
Section: The Venezuelan Diasporamentioning
confidence: 99%